Hydrothermal liquefaction of biomass produced from domestic sewage treatment in high-rate ponds. (April 2018) - Couto, Eduardo Aguiar; Pinto, Filomena; Varela, Francisco; Reis, Alberto; Costa, Paula; Calijuri, Maria Lúcia
Abstract: This study evaluates the application of biomass produced from the treatment of domestic sewage in high-rate ponds (HRPs) as feedstock for the production of bio-oil via hydrothermal liquefaction (HTL). The effects of reaction time, temperature, and biomass/water ratio on the yield of bio-oil were assessed. In addition, a balance of carbon and nitrogen among the products (bio-oil, aqueous phase, solid residue, and gas) was carried out, in order to evaluate the quality of the bio-oil and possibilities for increasing value from the byproducts. In a 15-min operation at 300 °C with biomass/water ratio of 1/10 (w.w −1 ), the bio-oil yield was of 44.4% (Dry Ash Free - daf-basis). Under every condition tested, the solid residue was the most abundant byproduct, mostly due to the high ash content in the biomass. The minimum nitrogen recovery in the bio-oil was 57%, obtained in the operation at 275 °C, which is considered the main disadvantage of the process. The use of biomass directly after its production may result in an excessive consumption of energy due to the high water content. However, the need for drying is reduced when compared to other microalgal-based bioenergy production processes, potentially achieving a positive energy balance in the HTL. Graphical abstract: Highlights: Bio-oil yields up to 44% were obtained. Reaction time above 15 min did not provide significant yield gains. Temperatures higher than 300 °C favored the bio-oil formation. The energy balance of HTL was positive in many operational conditions. N content in bio-oil was high, which constitutes the main challenge for the process.